Gerenciamento global de talento: estudo em uma Companhia Internacional de Tecnologia da Informação - Mazurkiewicz, Ligia Zotini (2011)
The aim of the present research is to analyze the culture of Global Talent Management in an IT multinational company, its processes, and the career expectations of those participating in this program. The study was motivated by the company's result in a survey on global leadership training, in which it was classified in 2009 by the consulting firm Hewitt Associates, as the global company that better developed leaders in the corporate world. This is a case study with exploratory and descriptive purposes. The data collection was done with 55 high performers from different areas, ages, and with long careers in business. In the end, 30 professionals completed the questionnaire, which revealed that the company's talents recognize GTM programs and have positive expectations regarding the growth of their international careers by being part of them. They also recognize that their careers rely heavily on their personal efforts, although highlighting that leadership plays a direct role in the evolution and maintenance of such positions over time